PERLINDUNGAN HUKUM KREDITUR DAN DIBITUR MENURUT UNDANG-UNDANG NOMOR 21 TAHUN 2008 TENTANG PERBANKAN SYARIAH : Legal Protection Of Creditors And Debtors According To Law Number 21 Of 2008 Concerning Sharia Banking - Baiq ermayanti (Fakultas Hukum Universitas Gunung Rinjani, 2023)
This research aims to find out and analyse the legal protection of creditors and debtors according to law number 21 of 2008 concerning sharia banking. In this research, the researcher formulated the problem, what is the form of legal protection for creditors and debtors in sharia banking, and how to implement prudential principles in anticipating bad credit in sharia banking. This research requires normative juridical research which researchers carry out by examining library materials or secondary data. In this research, a statutory approach is used which is related to the principle of prudence in sharia banking. According to Law no. 21 of 2008 concerning Sharia Banking. Next, using conceptual (conceptual approach) is used to examine general points of view and principles that apply in law, such as literature or references that are relevant to the research object. The research results show that the banking principle of prudence is a principle that is anticipatory in preventing the possibility of banks suffering losses in distributing funds to customers, then the principle of prudence in carrying out its business activities and is obliged to uphold and adhere to this principle further if in In the most common case, such as a debtor stumbling over bad credit, resolution efforts can be taken in two ways, namely litigation efforts through the courts, and non-litigation efforts through preventive efforts, namely actions to anticipate the emergence of bad credit, early warnings, and negotiation efforts.